(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
Social character education is one of the key priorities in the national education system, particularly at the junior high school level, which represents a crucial developmental stage for adolescents. This study aims to analyze the development of students’ social character through the internalization of Ahlussunnah wal Jamaah (Aswaja) values in Social Studies learning at SMP Fauzaniyyah Garut. A qualitative approach with a phenomenological method was employed, involving Social Studies teachers, the principal, the vice principal for curriculum affairs, and students as participants. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using Miles and Huberman’s model. The findings reveal that Aswaja values such as tawasuth (moderation), tawazun (balance), tasamuh (tolerance), and i’tidal (justice) were successfully integrated into Social Studies learning through teacher modeling, curriculum integration, and school culture. The internalization of these values contributed to the enhancement of students’ empathy, tolerance, cooperation, and social responsibility. These results highlight that Aswaja-based character education can serve as an effective strategy to address moral degradation among adolescents while reinforcing the goals of national education.